Droplet Self‐Propelling Control on Bioinspired Fiber in Low Temperature and High Humidity Environment. Issue 1 (3rd December 2019) - Hou, Yongping; Xing, Yan; Feng, Shile; Gao, Chunlei; Zhou, Hu; Zheng, Yongmei
Abstract: In low temperature and high humidity environment, the self‐propelling of droplet on normal wettable gradient surface is often out of control. Here, inspired by surface features of wetted spider silk and cactus, a kind of multilevel‐structure bioinspired fiber (BSF) with multigradients is fabricated via a novel gas‐bubble template‐assisted electrodeposition. The multilevel structures are used to control the state of the condensed droplets and make multigradients still work in low temperature and high humidity environment, while the multigradients provide multiple driving forces to overcome resistance. More importantly, one of driving forces, i.e., the coalescence driving force, can be controlled via the temperature. Therefore, the BSF can not only realize the desired self‐propelling of deposited droplet in low temperature and high humidity environment similar to wetted spider silk and cactus, but also present the controllability of movement. The results may assist in the design of functional surfaces required for cold environment or high humidity, e.g., low temperature microreactors, chemical analytics under specific conditions, and sensors. Abstract : Droplet self‐propelling control in low temperature and high humidity environment is realized on bioinspired fiber fabricated via a novel gas‐bubble template‐assisted electrodeposition method.